Research of the Pressure Angle Optimization of Main Reducer Gear based on ADAMS - Zhu Yunlong; Xu Jinli; Han Shaojun; Lu Lei; Liu Chuan (Jixie chuandong)
For the severe vibration and scream noise of a mini car main reducer in high- speed neutral coasting condition,the pressure angle of the main reducer hypoid gears is taken as the study object. A torsional vibration dynamics model of gears system is established,after changing the pressure angle on both sides of gear tooth in the UG model and importing into the ADMAS,the dynamics characteristics of the gear system with different pressure angle under the same coasting condition are studied and compared. It is concluded that the meshing vibration performance of main reducer gears system could be improved when the convex surface pressure angle of the passive gear tooth decreased 1° at the same time the concave surface pressure angle of the passive gear tooth increased 1°. The correctness of the simulation analysis is verified by experiments at last,and the research result could be applied to the design and manufacture of the main reducer gear.